A redesign of the toothpaste tube using green QFD II for improved usability and sustainability. (20th March 2023) - Angtuaco, Danielle S.; Barria, Nathan Mitchell A.; Lee, Joshua Matthew C.; Tangsoc, Jazmin C.; Chiu, Anthony Shun Fung; Mutuc, Jose Edgar
Abstract: Toothpaste tubes are commonly manufactured in the form of soft-body tubes made of aluminum laminate. Studies have shown, however, that this design poses problems with usability (difficulty in extruding toothpaste) and sustainability (difficulty in disposing or recycling of materials). While efforts have been made to alleviate these concerns, new designs fail to adequately address both problems jointly. For this reason, this paper aims to introduce a new design incorporating these two aspects for the benefit of its users and the environment. The Green Quality Deployment (GQFD) II methodology was therefore applied in this study as it employs a quantitative approach to developing products by addressing customer needs while also considering sustainability. It was then determined that a rigid, twistable tube made of polylactic acid (PLA) yielded the best mix of usability and sustainability considerations and was chosen among the other alternatives. This was supported by user feedback given that 6 of the 7 customer requirements showed an enhanced performance compared to the laminated tube, using the Welch's t -test having a p-value of less than 0.05. On average an improvement of 1.16 points (out of a scale of 5) was achieved. This suggests that the integration of both usability and sustainability in product design is possible without compromising on one aspect for the other and that sustainable products need not sacrifice functionality. Thus, it serves as a stepping stone towards achieving sustainable production and consumption by providing functional eco-friendly alternatives.